2022
DOI: 10.1128/iai.00568-21
|View full text |Cite
|
Sign up to set email alerts
|

Nontypeable Haemophilus influenzae Infection Impedes Pseudomonas aeruginosa Colonization and Persistence in Mouse Respiratory Tract

Abstract: Patients with cystic fibrosis (CF) experience lifelong respiratory infections which are a significant cause of morbidity and mortality. These infections are polymicrobial in nature, and the predominant bacterial species undergo a predictable series of changes as patients age. Young patients have populations dominated by opportunists that are typically found within the microbiome of the human nasopharynx, such as nontypeable Haemophilus influenzae (NTHi); these are eventually supplanted … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…aeruginosa resulted in cooperative infection with more significant inflammatory consequences following dual infection (Figs 3–5). These experiments are consistent with our published work seen in non-CF BALB/c mice [12, 13].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…aeruginosa resulted in cooperative infection with more significant inflammatory consequences following dual infection (Figs 3–5). These experiments are consistent with our published work seen in non-CF BALB/c mice [12, 13].…”
Section: Discussionsupporting
confidence: 93%
“…Our recent work showed that in experimental mouse respiratory infections, NTHi diminishes colonization and persistence of P. aeruginosa by priming of innate host defenses [12]. Conversely, in separate studies, we also showed that P.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations